2017
DOI: 10.5114/hpr.2017.63936
|View full text |Cite
|
Sign up to set email alerts
|

The influence of music therapy on quality of life after a stroke

Abstract: A stroke is an interruption in the course of one's life. It often results in physical disability, cognitive or executive disorders, emotional problems and, as a consequence, the decrease of one's quality of life. The goal of this research was to determine whether music therapy during neurorehabilitation can positively influence the assessment of one's quality of life after a stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Of 10 fitness training studies, four measured outcomes at baseline and post‐intervention (Aidar et al., 2016; Mahmood et al., 2022; Park et al., 2017; Reynolds et al., 2021), while the other studies followed up at 6, 12, or 15 months after interventions (Faulkner et al., 2015; Gjellesvik et al., 2021; Langhammer et al., 2008; Sandberg et al., 2016; Studenski et al., 2005; Vahlberg et al., 2017). Ten studies investigated psychological interventions, including cognitive‐behavioral interventions ( n = 5; Hjelle et al., 2019; Kerr et al., 2018; Majumdar & Morris, 2019; Visser et al., 2016; Wang et al., 2020), music therapy (MT; n = 3; Grau‐Sánchez et al., 2018; Poćwierz‐Marciniak & Bidzan, 2017; Raglio et al., 2017), and art‐based interventions ( n = 2; Kongkasuwan et al., 2016; Morris et al., 2019). The characteristics of the included studies and interventions are summarized in Tables 1 and 2, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of 10 fitness training studies, four measured outcomes at baseline and post‐intervention (Aidar et al., 2016; Mahmood et al., 2022; Park et al., 2017; Reynolds et al., 2021), while the other studies followed up at 6, 12, or 15 months after interventions (Faulkner et al., 2015; Gjellesvik et al., 2021; Langhammer et al., 2008; Sandberg et al., 2016; Studenski et al., 2005; Vahlberg et al., 2017). Ten studies investigated psychological interventions, including cognitive‐behavioral interventions ( n = 5; Hjelle et al., 2019; Kerr et al., 2018; Majumdar & Morris, 2019; Visser et al., 2016; Wang et al., 2020), music therapy (MT; n = 3; Grau‐Sánchez et al., 2018; Poćwierz‐Marciniak & Bidzan, 2017; Raglio et al., 2017), and art‐based interventions ( n = 2; Kongkasuwan et al., 2016; Morris et al., 2019). The characteristics of the included studies and interventions are summarized in Tables 1 and 2, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the above 15 physical intervention studies were diverse: Some reported improvements in both physical and mental QoL, while others reported improvements only in the physical domains of QoL. In the psychological category, mindfulness‐based cognitive thrapy (MBCT; Wang et al., 2020), ACT (Majumdar & Morris, 2019), problem‐solving therapy (Visser et al., 2016), MT (Grau‐Sánchez et al., 2018; Poćwierz‐Marciniak & Bidzan, 2017; Raglio et al., 2017), and creative art therapy (Kongkasuwan et al., 2016) were found to be beneficial to improve patients' QoL. Most of the above studies showed significant improvement in general QoL, including mental and physical QoL.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the neurofeedback sessions, reactions to different stimuli were verified, e.g. : a selected music genre may reduce the stress level significantly, something that can be noticed in the indicator results (Poćwierz-Marciniak, Bidzan, 2017). Each session lasted about 40 minutes.…”
Section: Therapeutic Framework Planmentioning
confidence: 92%